PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTU MULTIMEDIA ELEKTRONIK UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATERI BANGUN RUANG SISI DATAR KUBUS DAN BALOK KELAS VIII SMP KRISTEN 1 METRO TAHUN PELAJARAN 2020/2021 - Sari, Titis Arista Ratna (Jurnal Analisis Pendidikan Sosial, 2024)
In the era of industrial revolution 4.0, teachers felt challenged to deliver cyber-based learning with electronic multimedia. Electronic learning media are used by teachers to help increase student motivation and learning outcomes. According to Roestiyah (1998,20) the use of discovery techniques is that the teacher tries to increase student activity in the teaching and learning process. Meanwhile, based on the narrative of Kurniasih, et al (2014: 64-65), there are several shortcomings or weaknesses of Discovery Learning, one of which is that the essence in the Discovery Learning model will not be conveyed if it is used in the mindset of teachers and students who are comfortable with the old method. So, we need a new method using electronic multimedia for Discovery Learning. The research data collection method includes the documentation method in the form of daily test results for VIII grade students of SMP Kristen 1 Metro for the 2019/2020 academic year on cube and block material, the test method in the form of multiple choice questions. The data collection will be analyzed quantitatively in the form of numbers and then converted into qualitative information in the form of sentences. Student learning outcomes have increased from cycle I and cycle II after using the Discovery Learning learning model assisted by electronic multimedia on the material of the flat side space of cubes and blocks. The learning outcome data in the first cycle, there were 13 students who completed and 7 students who did not complete with a completeness percentage of 65%. In the second cycle, there were 15 students who completed and 5 students who did not complete with a percentage of 75% completeness. This increase has met the achievement indicator previously set at 75%. The conclusion of this research is that students' motivation and learning outcomes have increased from cycle I and cycle II after using the Discovery Learning learning model assisted by electronic multimedia on the material of the flat side space of the cube and the block.